Influences of person-environment fit, self-efficacy, working meaningfulness on work engagement and organizational commitment of lecturers at public universities in Ho Chi Minh City - Bui, Thi Nhi; Tieu, Van Trang; Tran, The Nam; Vo, Hoang Kim Uyen; Nguyen, Hoang Doan Anh (Journal of Finance - Marketing Research, 2023)
When the competition between universities becomes stronger, the maintenance and development of human resources, especially lecturers, becomes increasingly important. How to increase lecturers’ engagement with work and commitment with universities is an interesting question for both researchers and authorities. Based on the job demands-resources framework and social cognitive career theory, authors build the research model to analyze the impacts of lecturers’ perception about person-environment fit, self-efficacy and work meaningfulness on lecturers’ work engagement and organizational commitment. The mixed method is used with PLS-SEM analysis to analyze the data of 114 respondents. The influences of person-environment fit, and work meaningfulness are confirmed while the influence of self-efficacy is rejected. In theory, accepted hypotheses support the job demands – resources framework and social cognitive career theory. In practice, selecting carefully suitable candidates with job and with university is very necessary. Diversifying task in work is another solution to increase lecturers’ work engagement and organizational commitment.